Antiviral treatment of COVID-19: a clinical pharmacology narrative review (Medical Journal of Indonesia, 2020)
The outbreak of coronavirus disease 2019 (COVID-19) in December 2019 in China, has become a pandemic in March 2020. Repurposing old and relatively safe drugs becomes an advantageous option to obtain the urgently needed effective treatment. Repurposing chloroquine, hydroxychloroquine, oseltamivir, lopinavir/ritonavir, andfavipiravir, and the use of investigational drug remdesivir for treatment of COVID-19, are reviewed from the clinical pharmacology perspective, particularly its efficacy and safety. Limited clinical studies of chloroquine, hydroxychloroquine, favipiravir, and remdesivir showed some efficacy in COVID-19 treatment with tolerable adverse effects. Potential serious adverse effect of chloroquine and hydroxychloroquine is cardiac arrhythmia. Oseltamivir has no documented activity against SARS-CoV-2, while lopinavir/ritonavir showed limited efficacy in COVID-19. Currently, there is no sufficient evidence to recommend any specific anti-COVID-19 treatment. The decision to use these drugs during the COVID-19 pandemic must be based on careful consideration of the potential benefits and risks to the patient.